2018
DOI: 10.5380/abclima.v22i0.57776
|View full text |Cite
|
Sign up to set email alerts
|

Impactos Das Ondas De Frio Sobre a Saúde Pública No Município De São Joaquim - Santa Catarina - Brasil

Abstract: Para várias partes do mundo têm sido conduzidos estudos que tratam dos impactos dos extremos de temperatura sobre a saúde pública. Neste trabalho é apresentada uma análise da ocorrência de ondas de frio (OdF), assim como os impactos destes eventos no número de internações hospitalares do município de São Joaquim, Santa Catarina (SC), Brasil. Por meio de avaliações estatísticas, foram comparados dados de temperatura média do ar e de número de dias com OdF com dados de internações por doenças respiratórias e cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
2
0
6
Order By: Relevance
“…The herein collected data point towards warmer days and nights in many areas worldwide (WMO, ; IPCC, ). Moreover, many studies have shown the association between mortality/morbidity rates and cold/heat events (Montero et al ., ; Gao et al ., ; Gasparrini et al ., ; Linares et al ., ; Mills et al ., ; Orru and Åström, ; Tobías et al ., ; Silveira et al ., ; Geirinhas et al ., ). To mention a few examples in the Brazilian context, Son et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The herein collected data point towards warmer days and nights in many areas worldwide (WMO, ; IPCC, ). Moreover, many studies have shown the association between mortality/morbidity rates and cold/heat events (Montero et al ., ; Gao et al ., ; Gasparrini et al ., ; Linares et al ., ; Mills et al ., ; Orru and Åström, ; Tobías et al ., ; Silveira et al ., ; Geirinhas et al ., ). To mention a few examples in the Brazilian context, Son et al .…”
Section: Introductionmentioning
confidence: 99%
“…The herein collected data point towards warmer days and nights in many areas worldwide (WMO, 2010;IPCC, 2012). Moreover, many studies have shown the association between mortality/morbidity rates and cold/heat events (Montero et al, 2010;Gao et al, 2015;Gasparrini et al, 2015;Linares et al, 2015;Mills et al, 2015;Orru and Åström, 2017;Tobías et al, 2017;Silveira et al, 2018;Geirinhas et al, 2019). To mention a few examples in the Brazilian context, Son et al (2016), Bell et al (2008) reported the impact of temperature on mortality rates in the city of São Paulo (SP), and Geirinhas et al (2019) assessed such an impact in Rio de Janeiro.…”
Section: Introductionmentioning
confidence: 99%
“…Extremos frios também estão associados a problemas de saúde pública e desigualdade social. Silveira et al (2018) estudou o impacto das baixas temperaturas no número de internações hospitalares por doenças respiratórias e circulatórias em São Joaquim-SC. O autor verificou que o número de internações devido à pneumonia aumentou cerca de 39% durante as ondas de frio entre os anos de 1999 a 2013.…”
Section: Introductionunclassified
“…As temperaturas extremas, aqui designadas de ondas de calor (OdC) e de ondas de frio (OdF), são cada vez mais frequentes e geram consequências igualmente graves para os seres humanos como testemunham diversos autores (e.g. Guerreiro, 2011;Cunha, 2012;Monteiro, Carvalho, 2013;Mateus, 2014;Geirinhas et al, 2017;Geirinhas et al, 2018;Silveira et al, 2018).…”
Section: Introductionunclassified